Estimation of dynamic friction of the Akatani landslide from seismic waveform inversion and numerical simulation. Issue 3 (9th June 2016) - Yamada, Masumi; Mangeney, Anne; Matsushi, Yuki; Moretti, Laurent
Abstract: We performed numerical simulations of the 2011 deep-seated Akatani landslide in central Japan to understand the dynamic evolution of friction of the landslide. By comparing the forces obtained from numerical simulation to those resolved from seismic waveform inversion, the coefficient of the friction during sliding was investigated in the range of 0.1–0.4. The simulation assuming standard Coulomb friction shows that the forces obtained by the seismic waveform inversion are well explained using a constant friction of μ = 0.3. A small difference between the residuals of Coulomb simulation and a velocity-dependent simulation suggests that the coefficient of friction over the volume is well constrained as 0.3 most of time during sliding. It suggests the sudden loss of shearing resistance at the onset of sliding, that is, sudden drop of the initial coefficient of friction in our model, which accelerates the deep-seated landslide. Our numerical simulation calibrated by seismic data provides the evolution of dynamic friction with a reasonable resolution in time, which is difficult to obtain from a conventional runout simulation, or seismic waveform inversion alone.